Smoking cessation strategies for patients with asthma: improving patient outcomes - Perret, Jennifer L (J Asthma Allergy, 2016)
Smoking is common in adults with asthma, yet a paucity of literature exists on smoking cessation strategies specifically targeting this subgroup. Adverse respiratory effects from personal smoking include worse asthma control and a predisposition to lower lung function and chronic obstructive pulmonary disease. Some data suggest that individuals with asthma are more likely than their non-asthmatic peers to smoke regularly at an earlier age. While quit attempts can be more frequent in smokers with asthma, they are also of shorter duration than in non-asthmatics. Considering these asthma-specific characteristics is important in order to individualize smoking cessation strategies. In particular, asthma-specific information such as “lung age” should be provided and longer-term follow-up is advised. Promising emerging strategies include reminders by cellular phone and web-based interventions using consumer health informatics. For adolescents, training older peers to deliver asthma education is another promising strategy. For smokers who are hospitalized for asthma, inpatient nicotine replacement therapy and counseling are a priority. Overall, improving smoking cessation rates in smokers with asthma may rely on a more personalized approach, with the potential for substantial health benefits to individuals and the population at large.